Toward a constitutive model for cure dependent modulus of a high temperature epoxy during the cure - Zarrelli, M.; Skordos, Alexandros A.; Partridge, Ivana K. (Elsevier Science B.V., Amsterdam., 2010)
A constitutive model, based on Kohlrausch-Williams-Watts (KWW) equations, was developed to simulate the evolution of the dynamic relaxation modulus during the cure of a "high temperature' epoxy. The basic assumption of the modelling methodology proposed is the equivalence of the mechanisms underlying the evolution of the glass transition temperature and the relaxation time shift during the cure, leading to the use of a common potential function. This assumption is verified by the comparison of normalized glass transition data and principal relaxation times, which have been found to follow a single master curve. Results show satisfactory agreement between experimental data and model prediction over the range of chemical conversion considered.